EDUKASI PENINGKATAN PENGETAHUAN WALI MURID TENTANG IMUNISASI PADA SISWA PADA SD NEGERI 02 LADANG LAWEH DI KABUPATEN LIMA PULUH KOTA - Ayulia Fardila Sari ZA; Fatimatuz Zahra Batubara; Thiara Suci Budiman; Dian Muslimah; Arum Dira Diyana; Panesa Anggraila; Intan Berliana Marianda; Selsa Malia Putri (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
The achievement of complete basic immunization at the Situjuh Community Health Center, Limapuluh Kota Regency is very low, namely 17.8%. This figure is far from the target of 80%. Efforts are needed to increase parents' awareness of the importance of immunization in children. The aim of this activity is to provide education to increase the knowledge of parents/guardians about immunization in children. The community empowerment methods used are counseling and advocacy. This activity consists of: situation analysis, licensing, creating health promotion media in the form of leaflets and posters, advocacy counseling, and evaluation. The target audience is the parents/guardians of SDN 02 Ladang Laweh students. Target selection was based on recommendations from the Situjuh Community Health Center. Extension activities were carried out accompanied by the distribution of leaflets and posters. The counseling was attended by 27 parents of students which was held in the classroom at SDN 02 Ladang Laweh. As a result of the activity, there was positive acceptance and response from the parents regarding immunization for children. After counseling, advocacy was carried out at the school regarding the teacher's commitment to supporting immunization activities for children. Based on the evaluation results by analyzing pre and post-test questionnaires, there was an increase in parents' knowledge about immunization in children. It can be concluded that education in the form of counseling using leaflets and posters can increase the understanding and knowledge of parents/guardians of students at SD Negeri 02 Ladang Laweh regarding the importance of complete basic immunization in children.